A new laminopathy caused by an Arg133/Leu mutation in lamin A/C and the effects thereof on adipocyte differentiation and the transcriptome. (2nd January 2019) - Wang, Zhe; Dong, Yueting; Yang, Jing; He, Yingzi; Lin, Xihua; Wu, Fang; Li, Hong; Zheng, Fenping
ABSTRACT: We report a new laminopathy that includes generalized lipoatrophy, insulin-resistant diabetes, micrognathia and biopsy-proven, focal segmental glomerulosclerosis in a female, caused by a de novo heterozygous mutation R133L in the lamin A/C gene ( LMNA ). We analysed the nuclear morphology and laminar distribution in 3T3-L1 pre-adipocytes overexpressing human wild-type lamin A/C ( LMNA WT) or lamin A/C with the R133L mutation ( LMNA R133L). We found the nuclear size was varied, nuclear membrane invagination or blebbing, and an irregular A-type lamin meshwork in cells overexpressing LMNA R133L.3T3-L1 pre-adipocyte differentiation into adipocytes was impaired in cells expressing LMNA R133L; contemporaneously, the expression levels of genes associated with adipose tissue self-renewal, including adipogenesis, angiogenesis, and extracellular matrix maintenance, were downregulated. Furthermore, the insulin-signalling pathway was inhibited in LMNA R133L adipocytes. Microarray gene expression profiling showed that the most prominent differences between 3T3-L1 cells expressing wild-type LMNA and LMNA R133L were in genes implicated in metabolic pathways, the cellular response to DNA damage and repair. We thus expand the clinical spectrum of laminopathy and conclude that the LMNA R133L mutation associated with lipodystrophic features and multisystem disorders likely impairs adipocyte renewal and disrupts the expression of genes implicated in the induction and repair of DNA damage.